SISTEM OPERASIONAL UNIT PELAYANAN TERPADU SATU ATAP ( UPTSA ) SEBAGAI MODAL PELAYANAN SIPIL DINAS PERIZINAN PEMERINTAH KOTA YOGYAKARTA - Wicaksono, Baskoro (Nakhoda: Jurnal Ilmu Pemerintahan, 2014)
Prima Public Services are services that are under one roof agencies. In Yogyakarta, one-stopservice is realized in the form of the establishment of the ?Dinas Perizinan?, formerly known asOne-Stop Integrated Service Unit (UPTSA). The existence of this new service brings change inThe pattern of service so that it gets a good response from the public. This research wasconducted in Yogyakarta is First, How the production and distribution of "public services"Licensing Agency of Yogyakarta as a One-Stop Integrated Service Unit (UPTSA). Secondly,How Public Service standard form used to get Excellent Service award at the National Level.Third, how the public response to the quality standards of public service in the Department ofLicensing Yogyakarta. This study uses qualitative method with a phenomenological researchstrategy. Data collection techniques in this study using two ways, namely depth interview andreview of secondary documents. The result Showed UPTSA changes to "Dinas Perizinan" had apositive impact on service delivery, which formerly slow, non-transparent and unaccountableand unfriendly bertransformarsi be fast, transparent, responsive, friendly and accountable. On theother hand the use of information technology is a major weapon to simplify, improve and speedup service. This makes people give a positive response and appreciation of the quality of publicservices in the field of licensing.Keywords: Public Service, a one-stop service, Service Effectiveness